A numerical study on cooling performance of different type earth-air heat exchangers - Tasdelen, Fatih; Dagtekin, Ihsan (Pergamon-Elsevier Science Ltd, 2025)
Greenhouse gases released into the atmosphere are among the most important causes of climate change which affects the whole world today. The use of renewable energy sources should be encouraged in order to minimize greenhouse gas emissions increasing with the consumption of fossil energy sources. Energy consumption and greenhouse gas emission values of Earth-Air Heat Exchangers (EAHEs), which are systems based on renewable energy are quite low. In this study, analyses regarding the cooling performance of 3D-modeled different type (4 horizontal and 4 vertical) EAHEs with equal pipe lengths have been carried out in ANSYS FLUENT 19.2 software based on Computational Fluid Dynamics (CFD). The cooling performances of EAHEs have been examined within the Reynolds numbers range of (5x103 < Re < 105). Rises in the Reynolds number significantly influence the cooling efficacy of the EAHEs, whereas the soil thermal conductivity has less impact on their cooling efficiency. Mean air temperature reductions of 14.90 K and 18.44 K have been recorded for the Re = 5x103 value, while reductions of 8.12 K and 8.07 K have been seen for the Re = 105 value of the horizontal and vertical EAHEs, respectively. The energy savings for the EAHEs demonstrating better cooling performance over the summer season have been examined. The optimal energy saving for these EAHEs has been attained at the Reynolds number of 6x104. At the Reynolds number of 6x104, 378.048 kWh and 397.275 kWh of energy savings have been obtained for horizontal and vertical EAHEs, respectively. The maximum financial savings for H-model III and Vmodel IV EAHE over the summer season were 32.285 euros and 33.927 euros, respectively, at the Reynolds number of 6x104.
Keywords: Earth-air heat exchanger; Temperature; Cooling performance; Soil; CFD; Re number